Coronary Thrombolysis with Tissue-Type Plasminogen Activator: Prospective Review - Collen, Désiré (1984)
Coronary thrombolysis is not a goal in itself, but is employed to prevent necrotic dysfunction of jeopardized myocardial cells. It is being increasingly investigated as a treatment for acute myocardial infarction, which is often associated with thrombotic occlusion of an atherosclerotic coronary artery. The administration of thrombolytic agents has been shown to reopen an occluded coronary artery in the majority of such cases. Briefly summarized are studies performed to date in animal models and in patients with acute myocardial infarction.